Observational Methods for Assessing Ergonomic Risks for work-related musculoskeletal disorders. A Scoping Review (2018)
Introduction: Work-related musculoskeletal disorders (WRMSDS) are one of the most common causes of absence from work. Exposures in the work environment can cause or aggravate the impact of these musculoskeletal disorders and the identification of ergonomic exposures are essential in risk assessment. It is important to assess all three key indicators of these exposures (intensity, frequency and duration) for being able to estimate the risk level for the development of WRMSDS. Aim: This paper aims to give an overview of some of the observational methods that can be used for assessment of ergonomic risks in the workplace. Methods: This study was conducted as a scoping review of the medical and ergonomic literature and official governmental web pages in Sweden, U.S.A. and the Netherlands. Results: In total, 19 different observational methods were identified. We summarize our findings based on the body parts that were studied and what key indicators were assessed: 1) intensity of the workload (posture and force production), 2) frequency of the workload (e.g. repetitive movements), and 3) the duration of the workload (e.g. static work). In an appendix, we included a brief presentation of these methods together with the worksheet (if available) and the source reference of the observational method. Conclusion: For ergonomists that perform risk assessments, there is a large number of observational assessment tools available and it is important to understand that different methods can be used simultaneously to be able to estimate the objective risk levels for WRMSDS.